Review: The Chemistry, Toxicity and Antibacterial Activity of Curcumin and Its Analogues - Denison, Hannah J.; Schwikkard, Sianne L.; Khoder, Mouhamad; Kelly, Alison F. (Planta Medica, 2023)
Antimicrobial resistance is a global challenge that is already exacting a heavy price both in terms of human health and financial cost. Novel ways of approaching this crisis include the investigation of natural products. Curcumin is the major constituent in turmeric, and it is commonly used in the preparation of Asian cuisine. In addition, it possesses a wide range of pharmacological properties. This review provides a detailed account of curcumin and its analoguesʼ antibacterial activity against both gram-positive and gram-negative isolates, including its potential mechanism(s) of action and the safety and toxicity in human and animal models. We also highlight the key challenges in terms of solubility/bioavailability associated with the use of curcumin and include research on how these challenges have been overcome.
Keywords: Curcumin; Curcuma longa; Zingiberaceae; curcumin analogues; antibacterial; solubility; mechanism; toxicity